Are price limits really bad for equity markets? - Deb, Saikat Sovan; Kalev, Petko S.; Marisetty, Vijaya B. (Journal of Banking & Finance, 2010)
Despite widely documented criticisms, price-limit rules are present in many equity markets around the world. Using a game-theoretic model, we argue that, if the cost of monitoring a market is high, price-limit rules are beneficial. Empirical tests based on a cross section of 43 equity markets across five continents support our theoretical prediction. We find that the probability of the existence of price-limit rules is greater in markets that incur higher monitoring costs due to poorer business disclosure, more corruption and less efficiency in legal, regulatory and technological environments.